Preparation of macroporous scaffolds with holes in pore walls and pressure driven flows through them - Chatterjee, Soumyajyoti; Potdar, Aditi; Kuhn, Simon; Kumaraswamy, Guruswamy (RSC Advances, 2018)
Controlling the pore architecture in macroporous scaffolds has important implications for their use as reactor packings and as catalyst supports. We report the preparation of a macroporous structure, where the pore walls are perforated by holes. These materials are prepared by modification of the ice-templating protocol developed in our group. We freeze a dispersion of colloidal silica, polymer and cross-linker in a water/acetonitrile medium and allow crosslinking to proceed in the frozen state. The presence of a small fraction of acetonitrile (varying between 1.6% to 6.4%) results in the formation of holes in the pore walls. Increasing the acetonitrile concentration changes the pore size distribution, and produces smaller pores on average. This also results in an increasing fraction of the wall area being covered by small pores, of the order of a few microns in size. Perforation of the walls by pores does not change the overall porosity or modulus of the scaffolds. However, the introduction of pores leads to a drastic reduction in the pressure drop required to pump liquid through the scaffolds. The observed residence time distribution (RTD) in the scaffolds is represented by two plug flow reactors (PFRs) in parallel. The RTD results indicate that increasing the hole fraction in the pore walls results in increased channelling which explains the aforementioned decreased pressure drop during pressure driven flow.